Superparamagnetic Fe/Au Nanoparticles and Their Feasibility for Magnetic Hyperthermia - Mohamed F. Sanad; Bianca P. Meneses-Brassea; Dawn S. Blazer; Shirin Pourmiri; George C. Hadjipanayis; Ahmed A. El-Gendy (Applied Sciences, 2021)
Today, magnetic hyperthermia constitutes a complementary way to cancer treatment. This article reports a promising aspect of magnetic hyperthermia addressing superparamagnetic and highly Fe/Au core-shell nanoparticles. Those nanoparticles were prepared using a wet chemical approach at room temperature. We found that the as-synthesized core shells assembled with spherical morphology, including face-centered-cubic Fe cores coated and Au shells. The high-resolution transmission microscope images (HRTEM) revealed the formation of Fe/Au core/shell nanoparticles. The magnetic properties of the samples showed hysteresis loops with coercivity (HC) close to zero, revealing superparamagnetic-like behavior at room temperature. The saturation magnetization (MS) has the value of 165 emu/g for the as-synthesized sample with a Fe:Au ratio of 2:1. We also studied the feasibility of those core-shell particles for magnetic hyperthermia using different frequencies and different applied alternating magnetic fields. The Fe/Au core-shell nanoparticles achieved a specific absorption rate of 50 W/g under applied alternating magnetic field with amplitude 400 Oe and 304 kHz frequency. Based on our findings, the samples can be used as a promising candidate for magnetic hyperthermia for cancer therapy.